Factors associated with knowledge on blood donation among the undergraduates of University of Jaffna - Tharmini, N.; Vanavan, V.; Jegapragash, V.; Hettiarachchi, A.N. (University of Jaffna, 2024)
Blood is a vital and life-saving substance in medical emergencies. To ensure a steady supply of safe blood and blood products, a sufficient number of self-directed blood donors from the young population must be encouraged. For that, revealing the present knowledge on blood donation among them is significant. The aim of the study is toassess factors associated with knowledge on blood donation among undergraduates of University of Jaffna. An institution-based descriptive cross-sectional study was conducted among undergraduates from eight faculties of University of Jaffna. Data were collected by using pre-tested self- administered questionnaire from 370 participants. Data were analyzed using SPSS version 25 and participants’ knowledge was assessed based on their knowledge scores, with over 60% considered adequate and less than 60% considered inadequate. Association between knowledge and sociodemographic factors was identified using chi-squared test. Out of 370 participants, 61.9% (229) were female and mean age was 23.5 (SD=±0.985) years. Among them 27% were previously donated blood. From total respondents, only 25.4% had adequate knowledge on blood donation. The mean score for overall knowledge was 44.27% (SD=±9.171). More than half of the participants (59.7%) know the minimum recommended body weight for blood donation. Most of the participants (73.2%) know HIV can be transmitted by blood donation whereas only 35.7% of participants know syphilis can be transmitted by blood donation. There was a statistically significant association between knowledge and age (P= 0.027), nationality (P=0.05), residential area (P= 0.01) and academic year (P<0.001) and remarkably there was no significant association between knowledge and being a blood donor. The finding shows lack of knowledge regarding blood donation among the study population. Therefore, study suggests implementing awareness programs and distributing information leaflets on blood donation among targeted non-health related undergraduates will help to improve the level of knowledge.
Keywords: Blood donation; Knowledge; Undergraduates